Persistent Clones and Local Seed Recruitment Contribute to the Resilience of Enhalus acoroides Populations Under Disturbance - Dierick, Jasper; Phan, Thi Thuy Hang; Luong, Quang Doc; Triest, Ludwig (Frontiers in Plant Science, 2021)
Human-induced land use in coastal areas is one of the main threats for seagrass meadows globally causing eutrophication and sedimentation. These environmental stressors induce sudden ecosystem shifts towards new alternative stable states defined by lower seagrass richness and abundance. Enhalus acoroides, a large-sized tropical seagrass species, appears to be more resistant towards environmental change compared to coexisting seagrass species. We hypothesize that reproductive strategy and the extent of seedling recruitment of E. acoroides are altered under disturbance and contribute to the persistence and resilience of E. acoroides meadows. In this research, we studied eight populations of E. acoroides in four lagoons along the South Central Coast of Vietnam using 11 polymorphic microsatellite loci. We classified land use in 6 classes based on Sentinel-2 L2A images and determined the effect of human-induced land use at different spatial scales on clonal richness and structure, fine-scale genetic structure and genetic diversity. No evidence of population size reductions due to disturbance was found, however, lagoons were strongly differentiated and may act as barriers to gene flow. The proportion and size of clones were significantly higher in populations of surrounding catchments with larger areas of agriculture, urbanization and aquaculture. We postulate that large resistant genets contribute to the resilience of E. acoroides meadows under high levels of disturbance. Although the importance of clonal growth increases with disturbance, sexual reproduction and the subsequent recruitment of seedlings remains an essential strategy for the persistence of populations of E. acoroides and should be prioritized in conservation measures to ensure broad-scale and long-term resilience towards future environmental change.